Pendidikan Metakognitif Dalam Meningkatkan Kecerdasan Intrapersonal Siswa di MA Darul Ishlah - ., Ubaidillah (Universitas Muhammadiyah Makassar, 2024)
Intrapersonal intelligence is needed as an ability to guide oneself in advancing abilities and a more competent self. Therefore, it is necessary to increase this intelligence, one of which is through metacognitive education. Metacognition is considered to have a close correlation with intrapersonal intelligence, the concepts and theories have very relevant intersections to be correlated. This research is a type of Qualitative with a case study approach at MA Darul Ishlah Tulang Bawang Lampung. The methods used were interviews, observation and documentation, involving 24 students, 3 teachers and 2 leaders of the Darul Ishlah Foundation. The results of this study indicate that the stimulation of metacognitive development carried out on students during the learning process increases students' intrapersonal intelligence. Such as the ability to conceptualize life goals, manage emotions, motivate themselves and manage time effectively.